Care co‐ordination for older people in the third sector: scoping the evidence. (24th January 2017) - Abendstern, Michele; Hughes, Jane; Jasper, Rowan; Sutcliffe, Caroline; Challis, David
Abstract: The third sector has played a significant role internationally in the delivery of adult social care services for many years. Its contribution to care co‐ordination activities for older people, however, in England and elsewhere, is relatively unknown. A scoping review was therefore conducted to ascertain the character of the literature, the nature and extent of third sector care co‐ordination activity, and to identify evidence gaps. It was undertaken between autumn 2013 and summer 2014 and updated with additional searches in 2016. Electronic and manual searches of international literature using distinct terms for different approaches to care co‐ordination were undertaken. From a total of 835 papers, 26 met inclusion criteria. Data were organised in relation to care co‐ordination approaches, types of third sector organisation and care recipients. Papers were predominantly from the UK and published this century. Key findings included that: a minority of literature focused specifically on older people and that those doing so described only one care co‐ordination approach; third sector services tended to be associated with independence and person‐centred practice; and working with the statutory sector, a prerequisite of care co‐ordination, was challenging and required a range of features to be in place to support effective partnerships. Strengths and weaknesses of care co‐ordination practice in the third sector according to key stakeholder groups were also highlighted. Areas for future research included the need for: a specific focus on older people's experiences; an investigation of workforce issues; detailed examination of third sector practices, outcomes and costs; interactions with the statutory sector; and an examination of quality assurance systems and their appropriateness to third sector practice. The main implication of the findings is a need to nurture variety within the third sector in order to provide older people and other adults with the range of service options desired.